Peran Perilaku Etis Tenaga Penjual dalam Membentuk Kualitas Hubungan dan Loyalitas Pelanggan - Nunung Ghoniyah (Jurnal Aplikasi Bisnis, 2017)
This article explains about the important of ethical behavior of sales person to create customer loyalty trough relationship quality. It is very important especially for service business in order to the quality of service is not easy to measured. To evaluate quality service, consumer can see the tangible signals and interaction quality of front line employees. Unethical behavior of sales person such unhonest, force and unknow about product knowledge cause as low relationship quality (commitment and trust). Finally, relationship quality cause the customer willing or unwilling to make long term relationship with company.